Inulin protects against the harmful effects of dietary emulsifiers on mice gut microbiome - Cansu Bekar; Ozlem Ozmen; Ceren Ozkul; Aylin Ayaz (PeerJ, 2024)
Background The prevalence of inflammatory bowel diseases is increasing, especially in developing countries, with adoption of Western-style diet. This study aimed to investigate the effects of two emulsifiers including lecithin and carboxymethyl cellulose (CMC) on the gut microbiota, intestinal inflammation and the potential of inulin as a means to protect against the harmful effects of emulsifiers. Methods In this study, male C57Bl/6 mice were divided into five groups (n:6/group) (control, CMC, lecithin, CMC+inulin, and lecithin+inulin). Lecithin and CMC were diluted in drinking water (1% w/v) and inulin was administered daily at 5 g/kg for 12 weeks. Histological examination of the ileum and colon, serum IL-10, IL-6, and fecal lipocalin-2 levels were analyzed. 16S rRNA gene V3-V4 region amplicon sequencing was performed on stool samples. Results In the CMC and lecithin groups, shortening of the villus and a decrease in goblet cells were observed in the ileum and colon, whereas inulin reversed this effect. The lipocalin level, which was 9.7 ± 3.29 ng in the CMC group, decreased to 4.1 ± 2.98 ng with the administration of inulin. Bifidobacteria and Akkermansia were lower in the CMC group than the control, while they were higher in the CMC+inulin group. In conclusion, emulsifiers affect intestinal health negatively by disrupting the epithelial integrity and altering the composition of the microbiota. Inulin is protective on their harmful effects. In addition, it was found that CMC was more detrimental to microbiota composition than lecithin.